The Function of lncRNA LINC00997 as a Diagnostic Marker in the Progression of Esophageal Squamous Cell Carcinoma - Wang, Yongqiang; Pang, Dianxiang; Zhang, Xiao (Annals of clinical and laboratory science, 2023)
Early diagnosis of esophageal cancer can better improve patients survival and prognosis. Exploring the clinical significance of lncRNA LINC00997 expression in esophageal squamous cell carcinoma (ESCC) and evaluating its possibility as a diagnostic factor can help us understand the mechanism of ESCC. The serum of 95 patients with ESCC and 80 matched healthy subjects selected as the control group. The expressions of LINC00997 and miR-574-3p in serum and cells of ESCC were detected by RT-qPCR, and the relationship between LINC00997 and clinicopathological characteristics of patients was discussed. The diagnostic significance of LINC00997 for ESCC was reflected by ROC curve. The effect of silenced LINC00997 on cell biological function was investigated by CCK-8 and Transwell assays. Luciferase activity detection confirmed the targeting relationship of LINC00997 to miR-574-3p. Data showed that LINC00997 expression in serum and cells of ESCC was higher than that in healthy controls, whereas miR-574-3p was the opposite. The expression level of LINC00997 was correlated with lymph node metastasis and TNM stage in patients with ESCC. ROC curve found that the AUC value was 0.936, indicating that LINC00997 has the value of diagnosing ESCC. , silenced LINC00997 obviously reduced cell proliferation and growth ability, and its direct negative effect on miR-574-3p alleviated tumor progression. This study is the first to confirm that lncRNA LINC00997 may regulate the development of ESCC by targeting miR-574-3p, and to expound its potential as a diagnostic marker.